STRATEGI PETANI DALAM MEMUTUS MATA RANTAI KETERGANTUNGAN PADA TENGKULAK (STUDI DI DESA KOLUWOKA, KECAMATAN SUMALATA TIMUR KABUPATEN GORONTALO UTARA) - Pritika Dukalang; Funco Tanipu; Sahrain Bumulo (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
The dependence of farmers on middlemen remains a complex socio-economic issue in rural Indonesia. According to data from the Gorontalo Utara District Agricultural Office (2024), approximately 78% of farmers in Sumalata Timur Subdistrict continue to rely on middlemen for farming capital and crop distribution due to limited access to formal financial institutions. This study aims to analyze the forms of farmers' dependency on middlemen, the resulting socio-economic impacts, and the adaptive strategies employed to reduce such dependency in Koluwoka Village, Sumalata Timur Subdistrict, Gorontalo Utara Regency. The study employed a qualitative method with a case study approach, involving eight key informants consisting of farmers, village officials, and middlemen. Data were collected through in-depth interviews, field observations, and documentation. The findings reveal two main forms of dependency: economic dependency, which includes the need for agricultural capital, production facilities, and household necessities; and social dependency, characterized by reciprocal relationships based on trust and indebtedness. Middlemen not only serve as financial providers but also assist in meeting educational, household, and traditional ceremonial expenses, reinforcing an unequal patron-client relationship. Based on Robert Putnam's theory of social capital, the relationship between farmers and middlemen demonstrates strong bonding social capital within the community but weak bridging social capital connecting farmers to formal economic institutions. The adaptive strategies adopted by farmers to reduce dependency include forming independent farmer groups, establishing internal savings and loan activities, and collaborating with local cooperatives. The study implies the importance of strengthening social capital, improving financial literacy, and empowering farmers economically through inclusive access to capital and community-based institutional support.